Avaliação da resistência de união da interface adesiva de pinos de fibra de vidro e a dentina radicular - Brasil Neto, Aminthas Alves (2007)
The aim of this study was to assess the bond strength at the adhesive interface of fiber glass posts and root dentin, in three regions of the canal, fixed with three cementation systems. Twenty-four healthy human teeth, recently extracted for orthodontic or periodontal reasons, had their crowns removed at the cement-enamel junction with a diamond disk, under irrigation. The roots were endodontically treated and were filled with gutta percha and an endodontic cement containing eugenol (Endofil). One week after endodontic treatment ended, the obstruction was removed at a mean depth of 9mm in the cervical region of the root. The posts (Reforpost Fibra de Vidro No. 3) were cemented in the canals prepared with one of the three fixation systems described as follows (n = 8): in group 1 the Single Bond 2/ RelyX ARC system was used; in group 2 the ED Primer/Panavia 21 system, and in group 3 RelyX Unicem cement was used. All the cements and adhesive systems were used in accordance with the manufacturers’ instructions. Afterwards, the roots were sectioned in a cutting machine under irrigation, into three portions corresponding to the cervical, middle and apical thirds of the root canal region prepared for the post. The specimens were submitted to the pushout test in a universal test machine at a speed of 0.5 mm/min and the maximum bond strength values were recorded and submitted to statistical analysis (p < 0.05). Analysis of variance (ANOVA) showed statistically significant difference between the cervical, middle and apical thirds only for the Panavia 21 cement group, in which the apical third presented a lower mean bond strength value than the cervical and middle thirds (the Tukey´s test). When the bond strength in each region of the root was compared to assess the cementing materials, the analysis of variance (ANOVA) showed statistically significant different for the three regions of the canal. For the middle and apical thirds, the Panavia 21 cement presented significantly lower mean bond strength than the Single Bond 2/RelyX ARC and RelyX Unicem cements, these being statistically equal between them. For the cervical third, RelyX Unicem cement presented higher bond strength values than the Panavia 21 cement and the Single Bond 2/RelyX ARC cement was statistically equal to the other two materials.